2016
DOI: 10.1080/1745039x.2016.1253227
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the replacement of concentrate and fibre-rich hay by high-quality hay on chewing, rumination and nutrient digestibility in non-lactating Holstein cows

Abstract: The aim of this study was to investigate the effects of high-quality hay with an elevated sugar content alone or with graded amounts of concentrate feed on chewing and ruminating activity, apparent total tract digestibility (ATTD) and ruminal pH at different time points after feeding in the free ruminal liquid (FRL) and the particle-associated ruminal liquid (PARL). Eight rumen cannulated non-lactating Holstein cows were arranged in a Latin square design in four experimental runs lasting 25 d each. The four di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 35 publications
1
31
3
1
Order By: Relevance
“…High and variable intake of WSC by browsers is also expected in captivity. For example, the sugar content of roughages routinely fed to ruminants in captivity (grass or lucerne hay) may range from 5% to over 12% of DM (Hall, ; Kleefisch et al, ). Furthermore, in several studies fruits and vegetables accounted even for 15% of DM fed to zoo ruminants (Ritz et al, ; Taylor et al, ; Verkammen et al, ), which had to result in high intake of mono‐ and disaccharides (even over 15% of consumed DM).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High and variable intake of WSC by browsers is also expected in captivity. For example, the sugar content of roughages routinely fed to ruminants in captivity (grass or lucerne hay) may range from 5% to over 12% of DM (Hall, ; Kleefisch et al, ). Furthermore, in several studies fruits and vegetables accounted even for 15% of DM fed to zoo ruminants (Ritz et al, ; Taylor et al, ; Verkammen et al, ), which had to result in high intake of mono‐ and disaccharides (even over 15% of consumed DM).…”
Section: Introductionmentioning
confidence: 99%
“…High and variable intake of WSC by browsers is also expected in captivity. For example, the sugar content of roughages routinely fed to ruminants in captivity (grass or lucerne hay) may range from 5% to over 12% of DM (Hall, 2010;Kleefisch et al, 2017). Furthermore,…”
mentioning
confidence: 99%
“…However, increased dietary starch resulting in increased rumen volatile fatty acid (VFA) production has also been shown to increase VFA transport-related gene expression, resulting in a positive increase in energy uptake for the animal (18). While the fermentation of starch in the rumen in more rapid than the fermentation of forages, previous research from our lab has shown the beneficial effects of feeding high-quality hay (HQH) with an elevated content of sugars and metabolizable energy, which shifts the energy intake away from starch-rich concentrates and toward a healthier forage-based product (19). We found that the addition of such forages provides the rumen microbiota with digestible substrate for VFA production while also providing sufficient structural fiber to promote rumen pH buffering through rumination (19).…”
mentioning
confidence: 95%
“…While the fermentation of starch in the rumen in more rapid than the fermentation of forages, previous research from our lab has shown the beneficial effects of feeding high-quality hay (HQH) with an elevated content of sugars and metabolizable energy, which shifts the energy intake away from starch-rich concentrates and toward a healthier forage-based product (19). We found that the addition of such forages provides the rumen microbiota with digestible substrate for VFA production while also providing sufficient structural fiber to promote rumen pH buffering through rumination (19). Furthermore, it was seen that changes in the substrates provided with HQH resulted in changes in the digesta-associated microbiota of the rumen (20).…”
mentioning
confidence: 99%
“…Introduction It is common practise to feed high-yielding dairy cows high-grain diets. However, the disproportion between a high proportion of rapidly fermented carbohydrates and low physically effective NDF may cause impaired ruminal health through variation in the VFA and decreased ruminal fluid pH, which leads to SARA (Humer, 2017). Several studies have investigated the ethology and pathophysiology of SARA (Khafipour, 2009;Danscher, 2016), but still no clear definition of SARA exists.…”
Section: Methodsmentioning
confidence: 99%